South Korea and the intergovernmental multilateral organizations and forums of Latin America and the Caribbean (1993-2017) - Ramoneda, Ezequiel (2020)
This paper aims to analyze the relations of the Republic of Korea, also known as South Korea, with the countries of Latin American region as a whole, including the Caribbean ones, from their interactions in intergovernmental multilateral organizations and forums and the complement with other dialogue and cooperation mechanisms, such as official visits and links with specific group of countries grouped in regional trade blocks, between 1993 and 2017, encompassing the presidencies of Kim Young-sam, Kim Dae-jung, Roh Moo-hyun, Lee Myung-bak and Park Geun-hye. Leaving aside trade and investments, as well as migration flows, in which other Asian countries can also be highlighted, such as China or Japan, is hypothesized that South Korea has pursued an extra-regional middle-power foreign policy in inter-governmental multilateral organizations and forums in Latin America and the Caribbean. This work is not arguing whether or not Korea South is a middle-power in the international arena, but, in regard to its international relations with countries of Latin America, it behaves as a middle-power, or it considers itself as one.